Cardiac implant registries 2006-2016: a systematic review and summary of global experiences - Zhang, Shixuan; Gaiser, Sebastian; Kolominsky-Rabas, Peter (BMJ Open, 2018)
OBJECTIVES: The importance of Cardiac Implant Registry (CIR) for ensuring a long-term follow-up in postmarket surveillance has been recognised and approved, but there is lack of consensus standards on how to establish a CIR. The aim of this study is to investigate the structure and key elements of CIRs in the past decade (2006-2016) and to provide recommendations on 'best practice' approaches. SETTINGS AND PARTICIPANTS: A systematic search on CIR was employed in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The following databases were searched: the PubMed (Medline), ScienceDirect and the Scopus database, EMBASE. After identifying the existing CIRs, an aggregative approach will be used to explore key elements emerging in the identified registries. RESULTS: The following 82 registries were identified: 18 implantable cardioverterdefibrillator (ICD) registries, 7 cardiac resynchronisation therapy (CRT) registries, 5 pacemaker registries and 6 cardiovascular implantable electronic device registries which combined ICD, pacemaker and CRT implantation data; as well as 22 coronary stent registries and 24 transcatheteraortic heart valve implantation registries. While 71 national or local registries are from a single country, 44 are from European countries and 9 are located in USA. The following criteria have been summarised from the identified registries, including: registry working group, ethic issues, transparency, research objective, inclusion criteria, compulsory participation, endpoint, sample size, data collection basement, data collection methods, data entry, data validation and statistical analysis. CONCLUSIONS: Registries provide a 'real-world' picture for patients, physicians, manufacturers, payers, decision-makers and other stakeholders. CIRs are important for regulatory decisions concerning the safety and therefore approval issues of the medical device; for payers CIRs provide evidence on the medical device benefit and drive the decision whether the product should be reimbursed or not; for hospitals CIRs' data are important for sound procurement decisions, and CIRs also help patients and their physicians to joint decision-making which of the products is the most appropriate.
EVALuna2:35792

Exploring physicians and patients' perspectives for current interventions on thyroid nodules using a MCDA method - Karrer, Linda; Zhang, Shixuan; Kühlein, Thomas; Kolominsky-Rabas, Peter (Cost Effectiveness and Resource Allocation, 2021)
Background The detection of thyroid cancer has rapidly increased over last few decades without an increase in disease specific mortality. Several studies claim that the diagnose of thyroid nodules through routine ultrasound imaging is often the trigger for cascade effects leading to unnecessary follow-up over many years or to invasive treatment. The objective of this study was to explore physicians' and patients' insights and preferences regarding the current interventions on thyroid nodules. Methods An online survey was developed using a comprehensive multi-criteria decision analysis (MCDA) framework, the EVIdence based Decision-Making (EVIDEM). The EVIDEM core model used in this study encompassed 13 quantitative criteria and four qualitative criteria. Participants were asked to provide weights referring to what matters most important in general for each criterion, performance scores for appraising the interventions on thyroid nodules and their consideration of impact of contextual criteria. Normalized weights and standardized scores were combined to calculate a value contribution across all participants, additionally differences across physicians and patients' group were explored. Results 48 patients and 31 physicians were included in the analysis. The value estimate of the interventions on thyroid nodules reached 0.549 for patients' group and 0.5 was reported by the physicians' group, compared to 0.543 for all participants. The highest value contributor was 'Comparative effectiveness' (0.073 +/- 0.020). For the physicians' group, 'Comparative safety' (0.050 +/- 0.023) was given with higher value. And for the patients' group, 'Type of preventive benefits' (0.059 +/- 0.022) contributed more positively to the value estimation. 51% participants considered 'Population priorities and access' having a negative impact on the interventions of nodules.66% participants thought that the 'system capacity' had a negative impact. Conclusion Our study shows participants' preferences on each criterion, i.e., physician indicated keeping the interventions safe and effective more important, patients indicated quality of life after receiving interventions more important. Through comparison among participants, differences have been highlighted, which can make better communication between physicians and patients. This study provides a supportive decision-making for healthcare providers when they explored the interventions on thyroid nodules.
CRIS-Team WoS Importer:2021-05-21

Recalls of cardiac implants in the last decade: what lessons can we learn? - Zhang, Shixuan; Kriza, Christine; Schaller, Sandra; Kolominsky-Rabas, Peter (PLoS ONE, 2015)
BACKGROUND: Due to an ageing population and demographic changes worldwide, a higher prevalence of heart disease is forecasted, which causes an even higher demand for cardiac implants in future. The increasing high incidence of clinical adverse events attributed especially to high-risk medical devices has led an advocated change from many stakeholders. This holds especially true for devices like cardiac implants, with their high-risk nature and high complication rates associated with considerable mortality, due to their frequent use in older populations with frequent co-morbidities. To ensure patients' safety, the objective of this study is to analyze different cardiac implants recall reasons and different recall systems, based on an overview of the recalls of cardiac implant medical devices in the last decade. On the basis of the results from this structured analysis, this study provides recommendations on how to avoid such recalls from a manufacturer perspective, as well as how to timely react to an adverse event from a post-surveillance system perspective. METHODS AND FINDINGS: A systematic search of cardiac implant recalls information has been performed in the PubMed, ScienceDirect and Scopus databases, as well as data sources in regulatory authorities from 193 UN Member States. Data has been extracted for the years 2004-2014 with the following criteria applied: cardiac implant medical device recalls and reasons for recall, associated harm or risk to patients. From the data sources described above, eleven regulatory authorities and 103 recall reports have been included in this study. The largest cardiac implant categories include ICDs 40.8%, pacemakers 14.5% and stents 14.5%. Regarding the recall reasons, the majority of reports were related to device battery problems (33.0%) and incorrect therapy delivery (31.1%). From a total of 103 recall reports, five reported death and serious injuries. Our review highlights weaknesses in the current cardiac implant recall system, including data reporting and management issues and provides recommendations for the improvement of safety information and management. CONCLUSION: Due to the mortality associated with the nature of cardiac implants, the traceability and transparency of safety hazards information is crucial. By a structured analysis of recall reasons and their efficient management, important knowledge is gained to inform an effective safety-reporting system for monitoring the safety of cardiac implanted patients, ideally by building up cardiac implant registries worldwide in the future.
EVALuna2:35799